An insight into embryogenesis interruption by carbon nitride dots: can they be nucleobase analogs?. Issue 47 (22nd November 2022) - Zhou, Yiqun; Chen, Jiuyan; Kirbas Cilingir, Emel; Zhang, Wei; Gonzalez, Lemay; Perez, Samuel; Davila, Arjuna; Brejcha, Nicholas; Gu, Jun; Shi, Wenquan; Domena, Justin B.; Ferreira, Braulio C. L. B.; et al.
Abstract : Abstract : The carbon nitride dot (CND) is an emerging carbon-based nanomaterial. It possesses rich surface functional moieties and a carbon nitride core. Spectroscopic data have demonstrated the analogy between CNDs and cytosine/uracil. Recently, it was found that CNDs could interrupt the normal embryogenesis of zebrafish. Modifying CNDs with various nucleobases, especially cytosine, further decreased embryo viability and increased deformities. Physicochemical property characterization demonstrated that adenine- and cytosine-incorporated CNDs are similar but different from guanine-, thymine- and uracil-incorporated CNDs in many properties, morphology, and structure. To investigate the embryogenesis interruption at the cellular level, bare and different nucleobase-incorporated CNDs were applied to normal and cancerous cell lines. A dose-dependent decline was observed in the viability of normal and cancerous cells incubated with cytosine-incorporated CNDs, which matched results from the zebrafish embryogenesis experiment. In addition, nucleobase-incorporated CNDs were observed to enter cell nuclei, demonstrating a possibility of CND–DNA interactions. CNDs modified by complementary nucleobases could bind each other via hydrogen bonds, which suggests nucleobase-incorporated CNDs can potentially bind the complementary nucleobases in a DNA double helix. Nonetheless, neither bare nor nucleobase-incorporated CNDs were observed to intervene in the amplification of the zebrafish polymerase-alpha 1 gene in quantitative polymerase chain reactions. Thus, in conclusion, the embryogenesis interruption by bare and nucleobase-incorporated CNDs might not be a consequence of CND–DNA interactions during DNA replication. Instead, CND–Ca 2+ interactions offer a plausible mechanism that hindered cell proliferation and zebrafish embryogenesis originating from disturbed Ca 2+ homeostasis by CNDs. Eventually, the hypothesis that raw or nucleobase-incorporated CNDs can be nucleobase analogs proved to be invalid.